Review of Cult Fiction and Cult Film: Multiple Perspectives edited by Marcel Arbeit and Roman Trušník Palacký University in Olomouc, 2008 (American & British Studies Annual, 2009)
Review of Cult Fiction and Cult Film: Multiple Perspectives edited by Marcel Arbeit and Roman Trušník Palacký University in Olomouc, 2008